PENGETAHUAN ASUPAN ENERGI, AKTIVITAS FISIK, DURASI PENGGUNAAN GADGET DAN KEJADIAN KEGEMUKAN PADA SISWA SEKOLAH DASAR (Politeknik Kesehatan Kemenkes Bandung, 2022)
Obesity is a condition of weight that exceeds normal weight. The purpose of this study is to find out the picture of energy intake, physical activity, duration of gadget use and the incidence of obesity in students of The Great State Elementary School of Cirebon City. The study used cross sectional design, a sample used in the study of 37 students. Energy intake data collection uses the 24-hour recall method, while to determine physical activity using The Physical Activity Questionnaire for Children (PAQ-C) method and the duration of gadget use using questionnaires. The results showed students who had a sufficient energy intake of 89.2%, and more energy intake as much as 10.8%, low physical activity as much as 73% and high physical activity as much as 27%, the duration of high gadget use as much as 59.5% and the duration of low gadget use as much as 40.5%, students who had obese nutritional status as much as 78.4% and nutritional status.